Can Reducing Childhood Obesity Solve the Obesity Crisis in Australia?. Issue 5 (22nd April 2020) - Lung, Thomas; Baur, Louise A.; Bauman, Adrian; Hayes, Alison
Abstract : Objective: Childhood obesity prevention has been identified as a key strategy to address the obesity crisis, with considerable investment by governments internationally. This study modeled the implications of entering adulthood at a lower or higher BMI (a consequence of changes in childhood obesity) and modeled how this would influence future numbers of adults with obesity in Australia. Methods: In this study, a dynamic population model was used to investigate how obesity prevention in children could impact the future number of adults with obesity in Australia from 2015 to 2040. The base population was a nationally representative data set of 14, 256 individuals (representing approximately 17 million adults) from the Australian Health Survey 2014‐2015. Each year, a new 20‐year‐old cohort was added to the simulated population, reflecting the transition to adulthood under scenarios of stable, increasing, or decreasing childhood obesity. Results: Targeting and reducing childhood obesity will have only a small and delayed effect on adult obesity levels, with approximately 280, 000 fewer adults with obesity by 2040. Conclusions: These findings highlight the importance of investing in and implementing obesity prevention programs across all ages, particularly in young adults, to successfully reduce the prevalence of adult obesity in Australia.